Mechanical Ice Release Processes. I. Self-Shedding from High-Speed Rotors - Itagaki,K (1983)
Ice accreted on high-speed rotors operating in supercooled fog can be thrown off by centrifugal force, creating severe unbalance and dangerous projectiles. A simple force balance analysis indicates that the strength of accreted ice and its adhesive strength can be obtained by measuring the thickness of the accretion, the location of the separation, the rotor speed, and the density. Such an analysis was applied to field and laboratory observations of self-shedding events. The results agree reasonably well with other observations. (Author)